The great plunge in oil prices: Causes, consequences, and policy responses - John Baffes; M. Ayhan Kose; Franziska Ohnsorge; Marc Stocker (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
Following four years of relative stability at around 105 per barrel, oil prices have declined sharply since June 2014. This paper presents a comprehensive analysis of the sources of the recent decline in prices, and examines its macroeconomic, financial and policy implications. The recent drop in prices is a significant, but not an unprecedented event as it has some significant parallels with the price collapse in 1985-86. The recent decline has been driven by a number of factors: several years of upward surprises in the production of unconventional oil; weakening global demand; a significant shift in OPEC policy; unwinding of some geopolitical risks; and an appreciation of the U.S. dollar. Although the relative importance of each factor is difficult to pin down, OPEC's renouncement of price support and rapid expansion of oil supply from unconventional sources appear to have played a crucial role since mid-2014. The oil price drop will lead to substantial income shifts from oil exporters to oil importers resulting in a net positive effect for global activity over the medium term. Although several factors could counteract its impact on global growth and inflation, the drop in oil prices will pose significant challenges for monetary, fiscal, and structural policies.
Keywords: Q40; Q41; Q43; F40; E32; E62; 330; commodity prices; 2014 oil price decline; macroeconomic implications; supply factors; demand factors; unconventional oil production; global output; global inflation